Sociology of Space: The Elderly Activity Space Before and During the Covid-19 Pandemic (Komunitas, 2022)
The current pandemic has an impact on all lines of life, especially on elderly people with vulnerable or declining health status. Prior to the COVID-19 pandemic, the elderly were active in activities inside and outside their homes to fill their spare time in their old age, but during social restrictions and physical distancing, they were forced to stay in their homes for an indefinite time. Through qualitative methods, this research explores the activity space of elderly women who are still active in daily activities both at home and in their neighborhood before the pandemic and during the pandemic where government policies limit/influence the activities of the elderly. Participants of the research are 60 years old elderly women and over (WHO, 2020) who live in Banyumanik residence. The results showed that there was a decrease in the scale of the activity space used by the elderly during the pandemic, namely from the environmental space scale to the residential space scale.